The Effect of the Read-Aloud Method on Literacy and Critical Thinking Skills of Children Aged 5–6 Years - Uswatun Khasanah; Yes Mathoes Lasarus Malaikosa; Sri Setyowati (Journal Emerging Technologies in Education, 2026)
Background. Early childhood education plays a significant role in preparing children for future academic achievement, particularly in literacy and cognitive development. Preliminary observations at TK Banjarsari Asri, Cerme, Gresik, revealed that many children aged 5–6 years had not yet developed optimal literacy and critical thinking skills. Difficulties were identified in listening comprehension, retelling stories, using new vocabulary, asking questions, expressing opinions, and relating stories to personal experiences. Purpose. This study aims to analyze the effect of the read-aloud method on the literacy and critical thinking skills of children aged 5–6 years. Method. This study employed a quasi-experimental design involving children in Group B at TK Banjarsari Asri. The read-aloud method was implemented through interactive storytelling sessions using picture books entitled “Wake Up Early and Sleep Early” and “Love Learning and Socializing.” During the intervention, teachers encouraged children to listen actively, answer questions, predict story events, express opinions, and connect the stories to their daily experiences. Results. The findings indicate that the read-aloud method positively affected both literacy and critical thinking skills. Children showed improvement in listening comprehension, vocabulary acquisition, story retelling, oral communication, questioning ability, problem-solving, and expressing logical opinions. The interactive storytelling process also increased children’s participation and confidence during classroom activities. Conclusion. The read-aloud method can be considered an effective pedagogical strategy for improving literacy and critical thinking skills in early childhood education. Regular implementation of interactive read-aloud activities provides meaningful language experiences and supports children’s cognitive development.